PERBEDAAN PHYSICAL PERFORMANCE SISWA EKSTRAKURIKULER FUTSAL DAN SEPAKBOLA DI SMP NEGERI 1 TOBOALI - Sevin Sevin Sevin; Dedy Putranto; Muhammad Eka Mardyansyah Simbolon (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
This research was motivated by the fact that when doing futsal and football extracurricular activities, students experienced fatigue quickly for each team that competed and did not know the differences in the physical performance of futsal and football extracurricular students at SMP Negeri 1 Toboali. This study aimed to determine the differences in the physical performance of futsal and football extracurricular students at SMP Negeri 1 Toboali. This study used a quantitative method with a comparative type. The subjects in this study were all futsal and football extracurricular students of SMP Negeri 1 Toboali, totaling 28 people. Data collection techniques in this study were carried out using tests, including endurance, strength, speed, flexibility, balance, agility, and coordination. The data analysis technique used were the normality test, homogeneity test, and hypothesis testing using the paired samples T-test. Based on the results of statistical tests using the paired samples T-test (related T-test) between the physical performance data of football and futsal extracurricular students, the results obtained were the t-count value of 2.232. While with a significant level of 0.05, the t-table value was 1.771. It turned out that the value of the t-count was more significant than the value of the t-table (2.232 > 1.771). It showed that Ho was rejected and Ha was accepted, so it could be concluded that there is a significant difference in the physical performance of futsal and football extracurricular students at SMP Negeri 1 Toboali.